Clinical Application of Urologic Catheters, Devices and Products - Newman, Diane K. (Springer International Publishing, 2018)
Designed to provide a comprehensive and state-of-the-art overview of the use of urologic catheters and devices in clinical practice. Sections of the book have been structured to review the overall indication for the use of urologic catheters and devices, types available, complications and management. This text fills a critical need for resource materials on these topics. The book also includes highly practical presentations and of typical patients with catheters or devices seen in the clinical practice of geriatric urology, all in the form of case presentations with expert analysis and editorial commentary. Highlighting the integrated multidimensional aspects of care for urology patients, this book is unique in the inclusion of collaborating multidisciplinary authors who are all recognized experts in their field. Written entirely by urologic specialists, d valuable resource in the field of practicing urology, for urologists, nurse practitioners, physician assistants, and for those currently in training.